THREE ASPECTS (SELF, LEADERSHIP, AND ORGANIZATION) ARE IMPORTANT IN BUILDING WORK COMMITMENT - Yudhistira Adwimurti (Sekolah Menengah Kejuruan (SMK) Pustek, 2021)
The results will not betray effort, it is a real expression, that every success is the result of hard work, ability, intelligence, and sacrifice. This means that at work requires a committed attitude. Namely, a determination, sincerity, and responsibility for the trust received. Thus, every behavior is obedience to rules, obedience to orders, and compliance with procedures. The employee model with this attitude has a significant effect on the achievement of organizational goals. This study is interested in expressing the attitude of commitment and the variables that influence it. The research method used is quantitative, descriptive analysis, and path analysis. The results showed that the organizational culture variable was the dominant factor in commitment. Even organizational culture can increase morale (motivation) which has an impact on strengthening work commitment. In addition, the leadership variable has a weak relationship in explaining work motivation and commitment. This means that comfort, warmth, and good relations between employees are the main keys to generating morale. Then born an attitude of responsibility, fighting for the interests of the company, totality and loyalty to the progress of the company. At this point, culture becomes an important cause for the birth of employee dedication to the company.